Models of short bowel syndrome in pigs: a technical review - Weih, Sandra; Nickkholgh, Arash; Kessler, Markus; Frongia, Giovanni; Hafezi, Mohammadreza; Golriz, Mohammad; Fard-Rutherford, Nassim; Holland-Cunz, Stefan; Mehrabi, Arianeb (European surgical research, 2013)
Background: Short bowel syndrome (SBS) is still a life-threatening disease in both children and adults. Although the therapeutic options are improving, challenges still remain, and to overcome these challenges is a major focus of SBS research today. In order to simulate anatomical and physiological conditions similar to those in humans for research, porcine models of SBS are often used. Various approaches for generating SBS models have been described in the literature. Methods/Results: In this work, we present a review of different types of porcine models of SBS and outline the differences between those models regarding types of animals, surgical procedures, monitoring, and methods of assessment. Conclusion: The aim of this study was to select the most suitable SBS model regarding the purpose of the research.
Gesehen am 18.10.2021